Electrochemical hydrogen evolution reaction over Co/P doped carbon derived from triethyl phosphite-deposited 2D nanosheets of Co/Al layered double hydroxides. (1st March 2022) - Shu, Yasuhiro; Sasaki, Koki; Fujimoto, Yugo; Miyake, Koji; Uchida, Yoshiaki; Tanaka, Shunsuke; Nishiyama, Norikazu
Abstract: Hydrogen is widely considered an emissions-free alternative energy carrier for sustainable energy devices, such as fuel cells and nickel-metal hydride batteries. Recently, electrochemical hydrogen evolution reaction (HER) from water splitting has been attracted as an eco-friendly process for producing hydrogen. Herein, we report a Co/P-doped carbon material (Co/P/C) derived from cobalt-aluminum layered double hydroxide nanosheets (LDHs) for HER. The Co/P/C was synthesized using triethyl phosphite as phosphate and carbon sources by a one-step chemical vapor deposition (CVD) process. The regular arrangement of Co and Al atoms in the precursor LDHs allowed Co/P species to be highly dispersed under optimized CVD conditions. The carbon nanotube formed by the CVD process improved the catalytic activity of Co/P/C. The optimized Co/P/C exhibits a low overpotential of 240 mV at −10 mA cm −2 for HER, comparable to the commercial Pt/C catalyst. This work provides a new direction for developing transition-metal and hetero-atom co-doped carbon materials with high catalytic activity for HER. Highlights: Co/P-doped carbon materials are prepared by using layered double hydroxide. The metal aggregation was prevented by the unique of the layered double hydroxide. The deposition process using triethyl phosphite can introduce desire Co/P species. The synthesized Co/P/C shows excellent activity for HER in an acidic media.